1977
DOI: 10.1007/bf00520199
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional changes in pupal hypoderm in Drosophila melanogaster

Abstract: Transcriptional changes with development of the imaginal thoracic hypoderm of Drosophila melanogaster were evaluated by studies on pulse labeling and total composition with respect to protein. Evidence presented indicates that certain glycoproteins produced by prepupal salivary glands are important for bristle development long after the salivary gland is histolyzed. Striking changes in protein synthesis with development can be correlated with major hypodermal functions such as bristle formation, chitin deposit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1979
1979
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Variant tRNA-induced mistranslation affects a wide range of physiological processes and exerts both positive and negative effects on flies. Mistranslation is most deleterious during periods of intense growth and translational activity, including embryogenesis and pupation (Mitchell et al 1977;Mitchell and Petersen 1981;Trumbly and Jarry 1983;Qin et al 2007).…”
Section: Implications For Multicellular Eukaryotesmentioning
confidence: 99%
“…Variant tRNA-induced mistranslation affects a wide range of physiological processes and exerts both positive and negative effects on flies. Mistranslation is most deleterious during periods of intense growth and translational activity, including embryogenesis and pupation (Mitchell et al 1977;Mitchell and Petersen 1981;Trumbly and Jarry 1983;Qin et al 2007).…”
Section: Implications For Multicellular Eukaryotesmentioning
confidence: 99%
“…Due to the availability of a putative electrophoretic mutant of the KIL-1 protein, we could test for the presumption that prepupal salivary gland proteins contribute to the pupation fluid, which covers the external surface of the pupating animal (Mitchell et al, 1977b;Sarmiento and Mitchell, 1982). Samples of the wildtype pupation fluid were collected and the proteins analysed by SDS-PAGE.…”
Section: The Kil-1 Encoded Product Is Secreted Into the Pupation Fluidmentioning
confidence: 99%
“…The presence of predominant low molecular weight components among prepupal salivary gland proteins has been demonstrated in various Drosophila species (Mitchell et al, 1977b;Kress, 1982;Sarmiento and Mitchell, 1982;Shirk et al, 1988). Hence, they might be major representatives of prepupal salivary gland function.…”
Section: Introductionmentioning
confidence: 98%
“…He has identified a group of essential antigens ("housekeeping" proteins), most of which are present in all stages and tissues studied, and a group of "luxury" antigens, which varies considerably with developmental stage and tissue type. Striking differences in patterns of protein synthesis, examined by sodium dodecyl sulfate (SDS)-polyacrylamide gel electrophoresis, has been shown in salivary glands, thoracic epithelium, and other Drosophila tissues labeled with [35S]methionine at various times during development [14][15][16]. Rodgers and Shearn [17], using two-dimensional gel electrophoresis, have shown that about 15 to 20% of the proteins synthesized in wing, leg, and eye-antenna1 imaginal disks are unique to either one disk type, or to specific pairs of disks.…”
Section: Introductionmentioning
confidence: 99%